Analisis Perbandingan Kinerja Keuangan pada Sebelum, Saat, dan Sesudah Pandemi Covid-19 - Azri, Hasriel Muhammad; Sumiati, Sumiati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
World Health Organization has declared that Covid-19 is a global pandemic. The outbreak has brought adverse impacts to various companies, particularly those engaged in consumer goods manufacturing. The objective of this research is to identify the different performances of five consumer goods companies before, during, and after the Covid-19 pandemic. This quantitative descriptive research uses one variable, i.e., an independent variable in the form of the companies’ financial ratios consisting of liquidity, solvability, activity, profitability, and market) the data was assessed using parametric hypothesis test (two paired sample t-test) and non-parametric hypothesis test (Wilcoxon signed-rank test). The results of the analysis indicate that there are significant differences in the profitability ratio of the consumer goods manufacturing companies; they are gross profit margin in 2020 and 2022 (during and after the pandemic) and net profit margin in 2018 and 2022 (during and after the pandemic). Significant differences were not found in the companies’ liquidity, solvability, activity, and market ratios between the periods of before, during, and after the pandemic. Abstrak WHO (world health organization) menetapkan covid-19 sebagai pandemi global yang menyebabkan dampak buruk kepada berbagai perusahaan khususnya perusahaan manufaktur sektor consumer goods. Tujuan dari penelitian ini untuk mengetahui perbedaan kinerja keuangan lima perusahaan sektor consumer goods dari sebelum, saat, dan sesudah pandemi covid-19. Metode dalam penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian deskriptif. Variabel yang digunakan dalam penelitian ini menggunakan satu variabel yaitu variabel independen berupa rasio keuangan perusahaan sektor consumer goods (rasio likuiditas, solvabilitas, aktivitas, profitabilitas, dan pasar). Data telah diuji menggunakan uji hipotesis parametrik (uji-t dua sampel berpasangan) dan non-parametrik (wilcoxon signed rank test). Hasil dari penelitian ini menunjukkan bahwa, terdapat perbedaan yang signifikan pada rasio profitabilitas lima perusahaan sektor consumer goods, yaitu gross profit margin tahun 2020 (saat) dan 2022 (sesudah) pandemi serta net profit margin tahun 2018 (sebelum) dan 2022 (sesudah). Namun tidak ada perbedaan yang signifikan pada rasio likuiditas, solvabilitas, aktivitas dan pasar pada sebelum, saat, dan sesudah pandemi covid-19.